Pengaruh Penggilingan POFA dan Fly Ash Terhadap Kuat Tekan Mortar dengan FAS 0,4 - Siti Aja Aulia; Syamsul Bahri; Sulaiman AR; Syaifuddin Syaifuddin; Gusrizal Gusrizal (Politeknik Negeri Lhokseumawe, 2022)
POFA and fly ash are wates in the palm oil industry and electric generating power plant. This study aims to reduce the volume of these wastes in the field by grinding and being a substitute for cement in mortar mixtures. POFA and fly ash were each mada into a mortar with a percentage of 20% of the cement used. Before being used, each waste was first grinding 1000 cycles, 2000 cycles, 3000 cycles using a Los Angeles machine and also used POFA and fly ash 100% passing sieve #No.16 and 100% passing sieve #No.200. Furthermore, each waste is made of 50 mm x 50 mm x 50 mm cube specimens and wiill be tested for compressive strength at age of 1, 3, 7, and 28 days and also being tested for their porosity. The results showed that passing sieve #No.16 it means fly ash didn’t grinding reached a compressive strength of mortar about 58,22 MPa and its pororsity was 10,98%. The compressive strength of the mortar exceeds the control mortar by 36,68 MPa in 28 days. So it cn be concluded that the mortar with passing sieve #No.16 of fly ash can reduce the pororsity of the mortar so that it improves the compressive strength of the mortar.